El estado emocional del miedo como paradigma discursivo en el asenso del político desde la receptividad del mensaje - Sánchez Gonzáles, Hada Miluska (Estudios sobre el Mensaje Periodístico, 2007)
The political speechs are perceived as a portion of the dialogue since the man lives in a community. These are restored in the speech acts in a semantic structure that identifies the significant before the meaning. It’s a strategy of the speech that uses code paradigms coming from the representative spaces that present probable worlds as possible worlds. Provoke emotive reactions in the receiver, mental constructions that are anchored in the systems of the arausal, in the emotional and physiological cognition in the connective way. Morover, get the receptive subject’s cohesion resorting to its sensibity on the stimulated information in relation to the emotional state of the fear.